Computerkriminalität im Europäischen Strafrecht Kompetenzverteilung, Harmonisierungen und Kooperationsperspektiven - Haase, Adrian (Mohr Siebeck, 2017)
Combatting computer crime requires transnational co-operation between law enforcement agencies as well as the harmonisation of criminal law. Adrian Haase assesses existing EU directives regarding cybercrime, and develops a network-specific definition to facilitate the demarcation of European and national competences.
PublicationDate: 20171106
Keywords: Internationales Strafrecht -- Staatliche Beihilfen -- öffentliche Aufträge -- Computerstrafrecht -- Familiencharta -- Familienkodex -- Internetkriminalität -- Eschatological -- Spiritual persons -- Cyberkriminalität -- Cyercrime -- Verfassungsrecht und Staatslehre -- Strafrecht allgemein -- Besonderes Strafrecht -- Strafprozess und Strafjustiz -- Europarecht